Application of optimization techniques to maximize uniform sales profit using the Simplex Method - Soesilo, Budi; Kurnia Sandy, Luqman; Imamah, Imamah (Jurnal Simantec, 2025)
The uniform sales industry in Indonesia often faces challenges related to resource limitations that affect sales profitability. CV. Titis Konveksi experiences difficulties in optimizing uniform sales to maximize profit. This study applies the Simplex Method, a linear programming approach, to determine the optimal sales combination that generates maximum profit. In addition, this research develops a web-based information system to automate the optimization calculation, allowing users to easily determine the most profitable sales combination. The system is developed using Flask as the backend framework, with PHP for the user interface and MySQL for managing sales data, constraints, and optimization results. The data collected are primary data consisting of sales quantities from January 2022 to December 2023, selling prices and profits per product, raw material usage, machine capacity, and available working days. System evaluation was conducted by comparing calculation results from the developed system with manual calculations using Microsoft Excel and optimization results from QM for Windows V5. Functionality testing was also carried out using black box testing. Based on the results of the functionality testing, all of the system's main functions successfully operated as expected. According to the optimization results applied in the system, the optimal product sales combination to achieve maximum profit consists of 4.085 units of almamater blazers and 1.572 units of graduation gowns, generating a maximum profit of IDR 132,001,700. Compared to CV. Titis Konveksi’s previous actual profit of IDR 102,859,000, the optimized sales strategy offers a potential increase of IDR 29,142,700. The developed web-based information system has been proven effective in improving CV. Titis Konveksi's profitability by providing more optimal sales recommendations.Keywords: Profit Optimization, Simplex Method, Linear Programming, Garment Industry.